(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The article shows the narrative and narratological relationship between two important characters of Proustian actress: the star of Third-Republic Theatre, Berma, and the young symbolist actress Rachel. According to Girard’s theories on desire, it shows that the two characters follow two different and irreconcilable ways: Berma represents the purification of desire, whereas Rachel represents the degradation of desire in the society life of the salons. The article makes the narrative analysis in relationship with the current historical poetics of actor’s art at the end of Nineteenth Century and at the beginning of Twentieth Century. It results an historical evaluation by Proust who appreciates the classical style of Berma and devalues the symbolist experimentations in the context of a critical conception of the temporality in art.